Game Sebagai Layanan (GAAS) Pada Platform Cloud Gaming Gameqoo - Kesuma Negara, I Putu Gede Gentha; Linawati, Linawati; Sukadarmika, Gede (Majalah Ilmiah Teknologi Elektro, 2023)
Today’s games have entered the next generation gaming phase or the highest generation in the world of gaming. In today’s rapid development of games, it requires users/players to have computers with higher specifications. There is a way for players to run games that have high specifications with computer devices that have low specifications, with cloud gaming technology. There is a cloud gaming server in Indonesia called Gameqoo. To find out the feasibility of a game that is played on a cloud gaming service, it requires parameters that will measure it from the game side and form the user side, namely Quality of Service and Quality of Experience. With the existence of cloud gaming services, the experience of playing games on computers with low specifications becomes light and has pretty good visual quality. This is evidenced by the packet loss value which is 0%, the delay and jitter has value are still in the good category, the use GPU usage is below 5%. The research questionnaire was designed in such a way with an answer scale called the MOS (Mean Opinion Score) to measure Quality of Experience, and an average score on the MOS rating of 4.15 which gets a Good score on the MOS assessment standard. Keywords— Cloud; Quality of Service; Quality of Experience; Mean Opinion Score